Public administrators as politicians in office - Zohal Hessami; Timo Häcker; Maximilian Thomas (International Tax and Public Finance, 2025)
Abstract We analyze whether mayors' prior occupation in the local public administration matters for their performance. In theory, mayors' professional background may shape their competence in bureaucratic tasks. We use the example of grant receipts for visible investment projects for which mayors must submit an extensive application to the state government. Our dataset includes 1,933 mayor elections (1993-2020) in the German state of Hesse to which we apply a sharp RD design for close mixed-background races. Mayors' background on average has no effect on grant receipts. Yet, public administrator mayors do attract more grants than outsider mayors when they are ideologically aligned with the council, raising the motivation to apply for grants in the first place. We conclude that the competence of public administrator mayors only matters when they are motivated to use it, i.e. this is an example where incentives are necessary for the effects of political selection to materialize.
Additional information: D73;D78;H71;H77;H83
Keywords: 330; Public administration; Professional background; Administrative skills; Political selection; Mayors; Investment grants